THE AUTHORITY OF THE STATE ADMINISTRATIVE COURT (PTUN) TO ADJUDICATE POSITIVE FICTITIOUS DECISIONS FROM A PERSPECTIVE OF JUSTICE - Laksono, Nowo; Nasution, Krisnadi; Budiarsih, Budiarsih (PT. Altin Riset Publishing, 2025)
The Administrative Court (PTUN) plays an important role in safeguarding the principles of legal certainty, justice, and protection of citizens' rights in Indonesia's administrative legal system. One of the emerging issues is positive fictitious decisions, which stipulate that if an administrative official does not issue a decision within a certain period, the petition is deemed to have been granted. This study aims to explore the authority of the PTUN in adjudicating positive fictitious decisions from a justice perspective. The method used is normative legal research that analyzes relevant regulations and their implementation in practice. The findings reveal that regulatory changes through Law No. 6 of 2023 have created legal uncertainty, reduced the PTUN's authority to adjudicate positive fictitious decisions, and created potential injustices for the public. This study recommends that the PTUN be granted the authority to adjudicate positive fictitious decisions while considering the principle of substantive justice, and the need for clearer regulations regarding oversight mechanisms within the automated administrative system. This study concludes that the removal of the PTUN's authority without clear alternative solutions contradicts the fundamental principles of the rule of law and has the potential to harm the public in accessing administrative justice.